Menelusuri Makna Keuntungan di Balik Bertahannya Angkutan Umum “Pedesaan” - Indriani Ayu Rimadani; Achdiar Redy Setiawan (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2018)
AbstractThis study aims to explore the deep meaning of profits seen from “rural” public transport drivers’ point of view in Kamal. This study is qualitative research which does not aim to generalize the results. A transcendental research method is used to explore the progress of the interview. The subjects of this study are rural transportation drivers who have worked for more than 20 years and have their own rural transportation in Kamal. The results of this study indicate that profits are interpreted as a form of both material and non-material. The profits as material are used to support the family needs and the cost of public transportation itself. Meanwhile, for the profits that are interpreted as a non-material form, namely inner satisfaction profits where they can help people who need transportation and spiritual profits by applying "flexible" cost. In spite of feeling anxiousness about their flexible cost, they believe that they will get more than what he gives to others.AbstrakPenelitian ini bertujuan untuk menggali kesadaran dua informan secara mendalam mengenai makna keuntungan yang dilihat dari sudut pandang sopir angkutan pedesaan di Kecamatan Kamal, Bangkalan-Madura. Penelitian ini menggunakan penelitian kualitatif dengan metode fenomenologi transcendental. Hasil penelitian menunjukkan keuntungan dimaknai sebagai bentuk materi digunakan untuk menghidupi keluarganya serta biaya angkutan pedesaan itu sendiri. Keuntungan dimaknai sebagai bentuk non materi yaitu keuntungan kepuasan batin dengan merasa bahagia membantu para masyarakat yang membutuhkan transportasi dan keuntungan spiritual dengan menerapkan tarif “fleksibel” dan tidak pernah merasa rugi membantu setiap penumpangnya, beliau akan mendapatkan rezeki yang lebih dari apa yang diberikannya kepada orang lain.